Analisis Kepuasan Pelanggan dan Kualitas Layanan Pengguna Online Transportasi In Drive - Justin Chandra; Andy Angkasa; William Tanjaya; Louis Valentino Chairus; Johnson Lowie (Politeknik Kampar, 2024)
his study uses linear regression analysis to see how customer satisfaction and their levels of satisfaction in In Drive Transportation services relate to each other. The results showed that there is a relationship between the customer satisfaction variable and their satisfaction rate. However, overall, a regression model can only explain a small part of the variable that affects the customer’s satisfaction level. The main results suggest that most variables included in this analysis cannot explain most variations in client satisfaction levels. This suggests that other variables, such as the overall user experience or external factors such as traffic conditions, may also have a significant but invisible influence on customer satisfaction levels in In Drive Transport. Further research is needed because of the limitations of this model to identify additional components that affect overall customer satisfying of this transport service. The next step is a more in-depth and comprehensive research to gain a better understanding of the components affecting customer satisfactions of In Drive transport.